Germination behaviour of seeds from herbicide treated plants of Chenopodium album L. - Tanveer,Asif (2009)
The carry-over effect of sub-lethal herbicides was investigated on the germination of seeds collected from surviving Chenopodium album plants, which had received 1/8, 1/8 twice, 1/8 three times, 1/4, 1/2, 1/1 doses of either pre-emergence ioxynil or post-emergence bentazone in a previous onion (Allium cepa) crop. Seeds were also collected from surviving C. album plants, which had received 1/4, 1/2, 1/1 of either pre-emergence pendimethalin, propachlor and linuron, or 1/8, 1/8 twice, 1/8 three times, 1/4, 1/2, 1/1 of post-emergence ioxynil or linuron in a previous leek (Allium porrum) crop. Seeds of surviving plants were collected and tested for germination at temperature of 5, 10, 15, 20 and 25°C. The effect of different temperatures on the total number of germinated seeds was significant. Germination was minimum at low temperatures (5°C or 10°C). Herbicides did not show any effect on germination of C. album and resulted in the same final germination percentage as seeds collected from the unsprayed control plots.